2019
DOI: 10.1093/europace/euz198
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal QT interval duration and its changes in preadolescents and adolescents practicing sport

Abstract: Aims Twelve-lead electrocardiogram (ECG) is an established tool in the evaluation of athletes, providing information about life-threatening cardiovascular diseases, such as long QT syndrome. However, the interpretation of ECG is sometimes challenging in children, particularly for the repolarization phase. The aim of this prospective, longitudinal study was to determinate the distribution of QT interval in children practicing sport and to evaluate changes in QT duration overtime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…15 All LQTS groups, both genotype-positive and negative, shortened their QTc by an average of 21 ms. Of note, most ECG studies in athletes point to longer QTc values compared with controls with a relatively modest, and clinically irrelevant, difference between 10 and 15 ms. 16 This probably accounts, at least in part, for the close to 20-ms shortening observed after the diagnosis-related reduction in physical activity among LQTS patients, who start from much longer baseline QTc values. A recent study 17 of adolescents practicing sports suggested, based on 5 subjects, that when QTc is >480 ms it does not normalize over time; our data do not support that view, provided, however, that detraining takes place.…”
Section: Clinical Factscontrasting
confidence: 99%
See 1 more Smart Citation
“…15 All LQTS groups, both genotype-positive and negative, shortened their QTc by an average of 21 ms. Of note, most ECG studies in athletes point to longer QTc values compared with controls with a relatively modest, and clinically irrelevant, difference between 10 and 15 ms. 16 This probably accounts, at least in part, for the close to 20-ms shortening observed after the diagnosis-related reduction in physical activity among LQTS patients, who start from much longer baseline QTc values. A recent study 17 of adolescents practicing sports suggested, based on 5 subjects, that when QTc is >480 ms it does not normalize over time; our data do not support that view, provided, however, that detraining takes place.…”
Section: Clinical Factscontrasting
confidence: 99%
“…The baseline characteristics of the study population are summarized in Table 1. Males were 65%, mean age at presentation was 18±10 years [median, 14 (IQR, [12][13][14][15][16][17][18]], ranging from 6 to 56 years (19 subjects >40 years of age). Most (81%) were competitive athletes, whereas for 19% physical activity was limited to recreational sports.…”
Section: Study Populationmentioning
confidence: 99%
“…A similar evolution of the QTc interval in athletes over time has been previously described in the literature (23).…”
Section: Ecg Findings In Athletes Vs High-school Studentssupporting
confidence: 82%
“…In recent years, the Fridericia correction formula has emerged as a more heart rate-independent alternative, but since it provides QTc values 25 ± 11 ms shorter than the Bazett formula, new reference values would be needed. 50,51 At present, we believe that the Bazett formula should continue to be used. A brief period of hyperventilation may be useful to raise the heart rate in athletes with profound sinus bradycardia.…”
Section: Qt Intervalmentioning
confidence: 99%
“…At low frequencies (heart rate <50 bpm) it underestimates the QTc, at high frequencies it overestimates it (heart rate >90 bpm). In recent years, the Fridericia correction formula has emerged as a more heart rate‐independent alternative, but since it provides QTc values 25 ± 11 ms shorter than the Bazett formula, new reference values would be needed 50,51 . At present, we believe that the Bazett formula should continue to be used.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%